2007
DOI: 10.1016/s0929-6646(08)60079-0
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Toxic Epidermal Necrolysis Induced by Carbamazepine Treatment in a Patient Who Previously had Carbamazepine-induced Stevens-Johnson Syndrome

Abstract: Toxic epidermal necrolysis (TEN) is a rare but life-threatening skin disease that is most commonly drug-induced. It has recently been suggested that Stevens-Johnson syndrome (SJS) belongs to the same group of skin disorders, although it has a lower mortality rate than TEN. We report the case of a 26-year-old male schizophrenic patient with a history of carbamazepine-induced SJS 5 years earlier. At the time of his current admission, he was admitted to our psychiatry department with acute agitation due to schizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…We assumed that SJS did not occur on the first administration of carbamazepine because the patient stopped taking the medication after a single dose, which is not enough dosage to trigger hypersensitivity reaction. Huang et al also reported a case of fetal toxic epidermal necrolysis induced by carbamazepine treatment in a patient who previously had carbamazepine-induced SJS [12]. It has been reported that higher daily doses of some drugs are associated with an increased risk of SJS compared to lower doses, as is the case for allopurinol [13].…”
Section: Discussionmentioning
confidence: 99%
“…We assumed that SJS did not occur on the first administration of carbamazepine because the patient stopped taking the medication after a single dose, which is not enough dosage to trigger hypersensitivity reaction. Huang et al also reported a case of fetal toxic epidermal necrolysis induced by carbamazepine treatment in a patient who previously had carbamazepine-induced SJS [12]. It has been reported that higher daily doses of some drugs are associated with an increased risk of SJS compared to lower doses, as is the case for allopurinol [13].…”
Section: Discussionmentioning
confidence: 99%
“…The other 3 patients (1 with EM and 2 with TEN) had attacks of similar severity when compared with the first episode [17]. Huang et al [18] reported a case of TEN induced by carbamazepine in a patient who previously experienced SJS induced by the same drug. However, there is no evidence that EM may recur as SJS/TEN.…”
Section: Discussionmentioning
confidence: 99%
“…The earliest signs are fever and malaise. The mortality rate is 30% and the morbidity is higher (9)(10)(11)(12)(13)(14)(15). Approximately 85% of patients develop a skin rash that is usually exanthematous but may include blistering eruptions such as erythema multiforme, Stevens-Johnson syndrome (SJS), toxic epidermal necrolysis (TEN) and perifollicular ⁄ non-follicular pustular eruptions.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence is 0.4-1.2 cases per million per year. The mortality rate is 30% and the morbidity is higher (9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation